State Support of Electric Vehicle Industry in China: the Driving Forces, Actions and Perspectives - Pelegov, Dmitry V.; Eremenko, Gleb A. (Economy of Regions, 2020)
Nowadays, the electrification of the automotive industry in some regions symbolises the transition to a sustainable economy. Moreover, these changes were initiated by regulatory authorities, and not only consumers and manufacturers. The article summarizes the results of the first decade of implementing Chinese governmental policy promoting sales of electric vehicles. Our goal is to acquaint the Russian-speaking audience with the successful practise of state support of the emerging industry. As we focused on reviewing and analysing the information, the main research method is the survey of open sources and academic literature. In the first part of the article, we reported the key role of China in the global electric vehicle market and identified the main driving forces in the transformation of the national automotive industry. In the second part, we closely examined the actions taken by the Chinese authorities to ensure an increase in the share of electric vehicles. In the third part, we summarised and analysed the possible short-term changes, as well as discussed the impact of the described processes on the global economy. The implementation of the aforementioned policy enabled a breakthrough, allowing Chinese automotive industry to reach the leading position in terms of sales and production of electric vehicles. Therefore, this research can be used for both the adoption of successful practice and analysis of the influence of the emerging electric vehicle industry on the Russian and global economy.